Empirically-Derived Effect Size Distributions of Interventions for Young Children on the Autism Spectrum. Issue 2 (4th March 2023) - Chow, Jason; Zhao, Hongyang; Sandbank, Micheal; Bottema-Beutel, Kristen; Woynaroski, Tiffany
ABSTRACT: Objective: The purpose of this study is to present a set of empirically derived effect size distributions to provide field-based benchmarks for interpreting the observed effects of interventions for young children on the autism spectrum, and for planning future studies. Method: We generated effect size distributions and reported quartile values for each by outcome domain, and by boundedness, proximity, and assessment approach using 1552 effect sizes from 144 early childhood autism intervention studies gathered for a previously published meta-analysis. Results: Quartile values represent considerable heterogeneity in effect size distributions across outcome domains, as well as variability as a function of outcome boundedness, proximity, and assessment approach. Conclusions: Our results serve as field- and outcome-specific benchmarks (e.g., contextual guides for small, medium, and large effects) that will help autism intervention researchers easily incorporate information from relevant prior empirical literature when conducting power analyses to plan for future studies. Benchmarks will also assist researchers seeking to interpret the magnitude of observed effects in clinical trials relative to the broader distribution of intervention effects on similar outcomes. Nuanced discussions that contextualize study findings in light of relevant empirical benchmarks will better assist practitioners in understanding the magnitude and scope of demonstrated change relative to studies with similar outcomes and selecting interventions for clinical practice. We discuss the limitations of these data, our analyses, as well as directions for future work.